2020
DOI: 10.1016/j.cegh.2019.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Gender preference among post-natal women for the next child: A study from coastal south India

Abstract: A balanced sex ratio is important for a stable society. However, son preference and discrimination towards the female gender has resulted in an adverse sex ratio. The objective of this cross sectional study was to assess the preference of women in post natal period, regarding gender of their next child. In this hospital based study 155 post-natal women from two tertiary care hospitals of Mangalore, in Karnataka State, India were interviewed using a semi-structured questionnaire. Data was analyzed using Statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(23 reference statements)
0
0
0
Order By: Relevance
“…Also, prenatal sex selection is more common in societies where abortion is common and ultrasonography is available. [ 17 ] Quantitative researches demonstrate that different populations favor sons[ 18 19 20 ] and also few studies have shown a neutral approach in terms of gender. [ 21 22 ] In India’s patriarchal society, women are pressured to access community-based, sex-selective identification, and female fetal abortion.…”
Section: Discussionmentioning
confidence: 99%
“…Also, prenatal sex selection is more common in societies where abortion is common and ultrasonography is available. [ 17 ] Quantitative researches demonstrate that different populations favor sons[ 18 19 20 ] and also few studies have shown a neutral approach in terms of gender. [ 21 22 ] In India’s patriarchal society, women are pressured to access community-based, sex-selective identification, and female fetal abortion.…”
Section: Discussionmentioning
confidence: 99%